Vascular endothelial growth factor A (VEGFA) modulates bovine placenta steroidogenesis in vitro - Sousa, Liza Margareth Medeiros de Carvalho; Campos, Danila Barreiro; Fonseca, Vanessa Uemura; Viau, Priscila; Kfoury Júnior, José Roberto; Oliveira, Claudio Alvarenga de; Binelli, Mario; Buratini Junior, José [UNESP]; Papa, Paula de Carvalho (Elsevier, 2012)
Our objectives were to investigate the possible role of VEGFA in bovine placenta steroid synthesis and to determine whether cloned derived placental cells present similar responses as non-cloned ones. Placental cells from cloned (term) and non-cloned (days 90, 150, 210 and term) pregnancies were isolated and treated with VEGFA (50 ng/ml) for 24, 48 or 96 h. Progesterone (P4) and estrone sulfate (E1S) were assessed by RIA, while aromatase P450-positive cells were quantified using the point counting test. The percentages of steroidogenic and non-steroidogenic populations were determined by flow cytometry. VEGFA augmented or decreased P4 and E1S concentrations as well as aromatase P450-positive cell density, depending on gestational age and time in culture. The percentage of steroidogenic cells was lower than that of non-steroidogenic ones for each culture time (P < 0.05). VEGFA treatment did not change the proportion of steroidogenic and non-steroidogenic cells. Placental cells derived from cloned pregnancies presented higher concentrations of E1S and P4 than the non-cloned group. However, aromatase P450-positive cells were similar between groups (P > 0.05). VEGFA treatment altered P4 and E1S levels in placental cells depending on type of gestation. These results suggest that VEGFA acts locally in the bovine placenta to modulate steroidogenesis during gestation, but in a different pattern between cloned and non-cloned derived placental cells at term. Therefore, this factor can be considered an important regulator of placental development and function.
Keywords: Progesterone; Estrone sulfate; VEGFA; Bovine placenta